Low concentrations of PAHs induce tolerance in nitrifying bacteria - Lindgren, J. Fredrik; Hassellöv, Ida-Maja; Landquist, Hanna; Dahllöf, Ingela (Frontiers in Marine Science, 2015)
The ability of marine microbes to develop tolerance to polycyclic aromatic hydrocarbons (PAHs) was examined in a 90-day experiment. PAH levels in sediment were increased 0.3 and 1.6 times compared to the control sediment. Day 30, 60 and 90 the microbes were re-exposed to PAHs in a short-term toxicity test to detect tolerance, where nitrification and denitrification were used as endpoints. In addition, molecular analysis of the microbial communities was performed to detect possible differences in proportions of nitrifying bacteria compared to total bacterial abundance (amoA/rpoB-ratio) between treatments and control. We here show PAH-induced tolerance in nitrifying microbial communities after 60 and 90 days of pre-exposure, as potential nitrification EC10-values were significantly higher in the low treatment (L) after 60 days and in both treatments after 90 days compared to control. Tolerance development in denitrification was not detected. Furthermore, the developed tolerance resulted in reduced nitrification efficiency, compared to control. It was also shown that the induced tolerance produced dissimilar amoA/rpoB-ratio between treatments and control, indicating that development of tolerance changed the community composition and that the development time depended on initial exposure. The results from this study have implications for future studies or environmental monitoring programs of long-term oil and PAH-contaminated sites. The possibility for development of tolerance needs to be taken into account and potential nitrification can be used for evaluation of marine microbial health. Furthermore, changed proportions of nitrifying microbes can alter the capacity of ammonium oxidizing in benthic marine sediments.